2009
DOI: 10.1002/em.20467
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction in human lung adenocarcinoma cells by oil‐soluble allyl sulfides: Triggers, pathways, and modulators

Abstract: DAS (diallyl sulfide), DADS (diallyl disulfide), and DATS (diallyl trisulfide) are major oil-soluble allyl sulfides (OAS) that represent major garlic constituents. The anticarcinogenic and antimutagenic effects of these substances have been extensively studied during the last decades. Previous reports suggest that induction of apoptosis by OASs might contribute to their chemopreventive effects. In this study, we report that OASs DADS and DATS induce significant apoptosis in human lung adenocarcinoma A549 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…Although DATS failed to modulate TPA-induced p38 MAPK activation (data not shown), the compound significantly attenuated the phosphorylation and the catalytic activity of JNK in TPA-stimulated mouse skin. In contrast, DATS induces apoptosis in various cancer cells through upregulation of JNK (32,33).…”
Section: Discussionmentioning
confidence: 97%
“…Although DATS failed to modulate TPA-induced p38 MAPK activation (data not shown), the compound significantly attenuated the phosphorylation and the catalytic activity of JNK in TPA-stimulated mouse skin. In contrast, DATS induces apoptosis in various cancer cells through upregulation of JNK (32,33).…”
Section: Discussionmentioning
confidence: 97%
“…Garlic oils contain major organosulfur compounds, including diallyl sulfide (DAS; 112 g/g), diallyl disulfide (DADS; 1,183 g/g), and diallyl trisulfide (DATS; 751 g/g), and minor amounts of many other volatile compounds (49). These compounds possess potent anticancer, antioxidant, and anti-inflammatory immune modulation activities and antimicrobial properties (2,30,71,72,79,83). The inhibitory effect of DASs against Bacillus cereus, Salmonella sp., and Vibrio cholerae (7,62,63), Staphylococcus aureus and Candida albicans (42,51), Helicobacter pylori (52,58), and Klebsiella pneu-moniae and Pseudomonas aeruginosa (17,37,53,73) were studied, and a recent report has shown that DASs were synergistically effective when combined with antibiotics against antibiotic-resistant strains of Escherichia coli, Enterobacter cloacae, E. faecalis, and Citrobacter freundii (80).…”
mentioning
confidence: 99%
“…The regulation of apoptosis is, therefore, the most important in the treatment of cancer (Fulda, 2010;Lawen, 2003;Reed, 2002). Accumulated evidences indicated that the most of chemotherapeutic agents halt tumor cells proliferation via induction of apoptosis (Saha et al, 2010;Wu et al, 2009;Zhang, 2002). We examined whether jaceosidin inhibited cell growth of T24 cells through the induction of apoptosis.…”
Section: Resultsmentioning
confidence: 99%